Simulación numérica de yacimientos aplicando refinamiento local - Cedillo Trejo, Uriel (My University, 2014)
Simulación numérica de yacimientos aplicando refinamiento local
Keywords: Simulación numérica de yacimientos aplicando refinamiento local